تأثيرطول مدة الاضاءة على نمو نبات الشعير - ريدة, عائشة; جريبيع, نادية; لهرم, ايمان; صحراوي, الزهرة (جامعة الوادي - University of Eloued, 2022)
Cultivation of cereal crops is of great importance in the world, includingbarley as it is included in the list of crops that provide global food security, as well as for its economic and agricultural importance. Light is one of the main environmental factors contributing to the growth of any plant due to its great importance and its role in many biological and physiological processes. In our study, with the aim of improving and increasing the plant production of barley, we conducted an experiment to find out the effect of changing the photoperiod based on 7 different treatments (24 hours of light, +2, +4 hours of lighting, 24 hours of darkness, -2 and -4 hours of lighting and a witness) on the barley plant and its effect On vegetative growth in terms of germination percentage, speed, rate of germination speed, germination index, seedling strength, root and stem length characteristics, wet and dry weights, leaf area and relative water content. And our results determined that the barley plant showed the best vegetative growth characteristics when treated with light (-4 hours of illumination) in terms of stem length, wet and dry weight, relative water content, root length, wet and dry weight of the leaf and leaf area. The best results were for treatment of 24 hours of darkness. The light has recorded the lowest results for most of the traits studied in our experiment.
التنوع الحيوي و فيزيولوجيا النبات
Keywords: plante d'orge; éclairage; نبات الشعير ، الإضاءة